2009
DOI: 10.1016/j.jacc.2009.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Restenosis After Treatment of Unprotected Left Main Disease With Drug-Eluting Stents

Abstract: DES restenosis in the ULM artery can be managed in most cases with a minimally invasive approach, achieving favorable early and late results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 10 publications
2
26
1
3
Order By: Relevance
“…Consistent with previous reports, 5,6 the present data show that the treatment of UDLM DES-ISR with further DES is a safe and effective option, regardless of the restenosis pattern or the initial strategy. By contrast, treatment with POBA, even where DES-ISR is focal, results in suboptimal outcomes, with TLR rates exceeding 40% at 2 years.…”
Section: Is Pci With Repeat Des Implantation An Acceptable Treatment?supporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous reports, 5,6 the present data show that the treatment of UDLM DES-ISR with further DES is a safe and effective option, regardless of the restenosis pattern or the initial strategy. By contrast, treatment with POBA, even where DES-ISR is focal, results in suboptimal outcomes, with TLR rates exceeding 40% at 2 years.…”
Section: Is Pci With Repeat Des Implantation An Acceptable Treatment?supporting
confidence: 93%
“…Moreover, few data are available on the treatment of in-stent restenosis (ISR) in this region. 5,6 The aim of this study was to evaluate the optimal PCI strategy for patients with unprotected distal bifurcation left main coronary artery ISR following DES implantation (UDLM DES-ISR) and to determine whether the initial strategy affects the outcome of target lesion revascularization (TLR) for the ISR.…”
mentioning
confidence: 99%
“…7,8) In addition, a recent observational study from Chinese investigators has shown that DES-based PCI was superior to CABG in reducing major adverse cardiac/cerebral events and bleeding complications among aged patients (average age 72.5, range 60-89) with nonprotected LMCA-disease. 9) However, restenosis of the DES implanted in LMCA is not uncommon (reaching 10% to 20%), [10][11][12] and it could theoretically provoke a broad myocardial ischemia, leading to a fatal outcome. According to a retrospective registry of 70 restenotic cases RA AND DCB FOR LM-ACS WITH RCA-CTO from 718 patients undergoing PCI with DES for LMCA disease, 30.8% and 29.4% of the restenotic cases presented with ACS and stable angina, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective registry of 70 restenotic cases RA AND DCB FOR LM-ACS WITH RCA-CTO from 718 patients undergoing PCI with DES for LMCA disease, 30.8% and 29.4% of the restenotic cases presented with ACS and stable angina, respectively. 10) In the registry, 59 restenotic cases underwent repeat PCI, 7 CABG, and 4 medical treatment alone. The PCI procedures included 34 additional DES implantations, 22 plain or cutting balloons, 2 rotational atherectomies, and 1 BMS implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non-distal ULMCA stenosis, previous studies show increased restenosis of distal ULMCA lesions, even in patients undergoing DES implantation, 14,34 and the restenotic area usually occurred at the ostia of LCX or LAD instead of that of the ULMCA per se. 35 To avoid injury during stent deployment, in some cases the operator may spare the LAD and LCX ostial areas in type 4 bifurcation lesions of the Lefevre classification, 36 in which both the LCX and LAD ostia have no significant stenosis. However, the protrusion of the edge of the stent into the LAD or LCX ostium may occur and cause subsequent restenosis of either the LCX or LAD ostium.…”
Section: Baseline Angiographic Features and The Selection Of Stent Anmentioning
confidence: 99%